Draft Second Five Year Plan (Revised) Part I - Memoranda State - Tripura - Planning Commission (Planning Commission)
Tripura comprises an area of 4116 sq. miles or about 26,34,340 acres out of which about 16,63,000 acres are forests. the soil is of alluvial nature adjacent to the rivers, and in the hilly regions the soil is in many places black loamy with this sand. Bounded on three sides by Pakistan’s eastern wing, the state has the appearance of an enclave. the newly-constructed Assam- Agartala road which winds through steep hills and deep forests provides the states only link with the rest of India.
State - Tripura